Growth of few-wall carbon nanotubes with narrow diameter distribution over Fe-Mo-MgO catalyst by methane/acetylene catalytic decomposition - Labunov, Vladimir A. (2013)
Few-wall carbon nanotubes were synthesized by methane/acetylene decomposition over bimetallic Fe-Mo catalyst with MgO (1:8:40) support at the temperature of 900°C. No calcinations and reduction pretreatments were applied to the catalytic powder. The transmission electron microscopy investigation showed that the synthesized carbon nanotubes [CNTs] have high purity and narrow diameter distribution. Raman spectrum showed that the ratio of G to D band line intensities of IG/ID is approximately 10, and the peaks in the low frequency range were attributed to the radial breathing mode corresponding to the nanotubes of small diameters. Thermogravimetric analysis data indicated no amorphous carbon phases. Experiments conducted at higher gas pressures showed the increase of CNT yield up to 83%. Mössbauer spectroscopy, magnetization measurements, X-ray diffraction, high-resolution transmission electron microscopy, and electron diffraction were employed to evaluate the nature of catalyst particles.